An architecture and compiler for scalable on-chip communication. - Jian Liang (IEEE Transactions on VLSI systems)
A dramatic increase in single chip capacity has led to a revolution in on-chip integration. Design reuse and ease of implementation have became important aspects of the design process. This paper describes a new scalable single-chip communication architecture for heterogeneous resources, adaptive system-on-a-chip (aSOC) and supporting software for application mapping. This architecture exhibits hardware simplicity and optimized support for compile-time scheduled communication. To illustrate the benefits of the architecture, four high-bandwidth signal processing applications including an MPEG-2 video encoder and a Doppler radar processor have been mapped to a prototype aSOC device using our design mapping technology. Through experimentation it is shown that aSOC communication outperforms a hierarchical bus-based system-on-chip (SoC) approach by up to a factor of five. A VLSI implementation of the communication architecture indicates clock rates of 400 MHz in 0.18-μm technology for sustained on-chip communication. In comparison to previously-published results for an MPEG-2 decoder, our on-chip interconnect shows a runtime improvement of over a factor of four.